Perancangan Sistem Informasi Pelunasan Biaya Pendidikan Berbasis Web di TK Tunas Bangsa - Imelda Sella Putri R Putri R; Kiky Zulkifli (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to design a web-based Education Fee Payment Information System at Tunas Bangsa Kindergarten. Payment processes such as tuition fees, uniforms, activities, and stationery are still recorded manually, causing problems such as lost data, recording errors, and late reporting. A web-based information system is needed to simplify payment management and improve data accuracy. The study used a descriptive qualitative approach with observation, structured interviews, and documentation techniques. Data analysis used the Miles and Huberman model, while system development followed the waterfall model, starting from needs analysis to testing. The results showed that the designed system was able to accelerate the recording process, reduce input errors, and facilitate payment monitoring and the creation of integrated financial reports. The developed web-based information system successfully minimized errors, accelerated reporting, and increased the effectiveness of financial administration.